2022
DOI: 10.1002/pc.26604
|View full text |Cite
|
Sign up to set email alerts
|

Application of polyfunctional nanomaterials for 3D printing

Abstract: The use of 3D printing is becoming more and more popular, and new applications in extrusion and photopolymerization are being discovered every day. Due to the unidirectional action of the materials used, it is necessary to develop polyfunctional composites that provide a complex of extrusion and photopolymerization processes for 3D printing technology. The current problem of 3D printing application is the availability of ineffective composite materials with deteriorated mechanical and damping properties, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…[48] These variables are defined by the material used, the nozzle dimension, and the printer type. Polylactic acid (PLA) [49][50][51][52] and acrylonitrile butadiene styrene (ABS) are the most widely utilized materials with this technology, along with polyethylene terephthalate glycol (PETG) [53][54][55][56] and other composites. To utilize multimaterials in FDM with multi-purpose products, it needs to be optimized for the mentioned variables.…”
Section: Extrusion-basedmentioning
confidence: 99%
“…[48] These variables are defined by the material used, the nozzle dimension, and the printer type. Polylactic acid (PLA) [49][50][51][52] and acrylonitrile butadiene styrene (ABS) are the most widely utilized materials with this technology, along with polyethylene terephthalate glycol (PETG) [53][54][55][56] and other composites. To utilize multimaterials in FDM with multi-purpose products, it needs to be optimized for the mentioned variables.…”
Section: Extrusion-basedmentioning
confidence: 99%
“…[ 54 ] In addition, nanomaterials can also enhance the product's mechanical properties to give it more photothermal effects and broaden its application scenarios. [ 55 ] The combination of nanomaterials and medical 3D printing provides a novel strategy for producing high‐quality multi‐functional integrated medical products.…”
Section: Introductionmentioning
confidence: 99%
“…The above advancements have led to increasing research interest in composite and nanocomposite development for 3D printing applications, with the promise of more robust or application-tailored materials. Studies have shown that the introduction of micro or even 2 of 17 nanofillers into polymeric matrices can increase the mechanical properties of the unfilled matrix up to a certain percentage [20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%